Modern motherhood : women and family in England, 1945 - 2000 - Davis, Angela 1981- (Gender in history, 2012)
This book examines women's experiences of motherhood in England in the years between 1945 and 2000. Based on a new body of 160 oral history interviews, the book offers the first comprehensive historical study of the experience of motherhood in the second half of the twentieth century. Motherhood is an area where a number of discourses and practices meet. The book therefore forms a thematic study looking at aspects of mothers' lives such as education, health care, psychology, labour market trends and state intervention. Looking through the prism of motherhood provides a way of understanding the complex social changes that have taken place in the post-war world. This book will consider how women's experiences of motherhood reveal the change in women's lives, gender relations, culture and society, family and community patterns, health and welfare, and the relationship between the family and the state, that took place in these years